HUBUNGAN ANTARA LAMA HARI RAWAT DENGAN ANTRIAN MASUK RUMAH SAKIT PADA PASIEN BPJS DI RS. ISLAM JEMURSARI SURABAYA - Ekawati, Agustina; Afridah, Wiwik (Universitas Nahdlatul Ulama Surabaya, 2015)
Since January to December, visits BPJS patients in Jemursari Islamic hospital increased average of 241 patients per month. On 27 December 2014 have an survey with ten BPJS patiens who 80% must waiting for the room. The purpose of this research is to find out the relation of the inpatiets waiting list with the long of BPJS inpatient who was gived the treatment in Jemursari Islamic hospital Surabaya. The design is cross-sectional analytic probability sampling is simple random sampling . The population of inpatient in Islamic hospital Surabaya are 181 people, for sample are 73 BPJS patients hospitalized in Jemursari Islamic Hospital Surabaya , being 73 ALOS of BPJS patients secondary data taken from medical records. The independent variable is the long of stay with instument is the secondary data from medical record and the dependent variable of the queue inpatient with the research instrument using questioner. The results showed long of stay or BPJS patient ALOS majority (74.0 %) patients were not standardized , and almost all (85.0 %) BPJS patients queuing to enter the hospital. The Fisher's Exact Test statistical shows that p = 0,029 and p < a =0,05 means H0 is rejected, there is relationship long of stay with the queue BPJS patient in Jemursari islamic Hospital Surabaya The conclusion of this research is if the long of stay not standard with the queue of BPJS patient is getting more. Because of the reason, the hospital is expected to more optimalizing the long of stay of inpatient or give more bed.